559 new students register at UMPSA for 2024/2025 session - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
GAMBANG, 8 March 2025 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dr. Yatimah Alias, took the opportunity to meet and welcome new Bachelor’s degree students for the 2024/2025 Academic Session who registered at UMPSA Gambang Campus today.